2021
DOI: 10.3390/v13010088
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toscana Virus and Sandfly Fever Sicilian Virus in European Bat Colonies Measured Using a Neutralization Test

Abstract: Toscana phlebovirus (TOSV) and Sicilian phlebovirus (SFSV) are endemic in the Mediterranean area where they are transmitted to humans by infected sandflies. Vertebrates of several species have been postulated to act as reservoirs of these viruses, but convincing evidence is still awaited. Among them, bats have been suggested, however documented evidence is lacking. Here we tested a total of 329 bats belonging to eight species collected from twelve localities in southern Spain for the presence of neutralizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In this study, we found for the first time SFSV and TOSV neutralizing antibodies in wild birds. Our results show rates of neutralizing antibodies that were among the highest ever detected in vertebrates (Alwassouf et al, 2016b;Ayhan et al, 2021). Moreover, if the cut-off is decreased and moved from 40 to 20, NT Abs against SFSV and TOSV would be observed in 59% and 58.5% of quails, respectively.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In this study, we found for the first time SFSV and TOSV neutralizing antibodies in wild birds. Our results show rates of neutralizing antibodies that were among the highest ever detected in vertebrates (Alwassouf et al, 2016b;Ayhan et al, 2021). Moreover, if the cut-off is decreased and moved from 40 to 20, NT Abs against SFSV and TOSV would be observed in 59% and 58.5% of quails, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…After 5 days (for TOSV) and 6 days (for SFSV), the microplates were read under an inverted microscope, and the presence (neutralization titer at 20, 40, 80, and 160) or absence (no neutralization) of the cytopathic effect was noted. Cutoff value for positivity was set at titer ≥40 as in previous studies ( Alwassouf et al, 2016b ; Ayhan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Old World, at least 250 million people have been exposed to Phlebovirus infections [ 9 , 10 ]. One of the main examples is TOSV, which is known as an emerging pathogen causing meningitis in the Mediterranean region, for which defined reservoirs have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%